2019
DOI: 10.1073/pnas.1904182116
|View full text |Cite
|
Sign up to set email alerts
|

Energy and air pollution benefits of household fuel policies in northern China

Abstract: In addition to many recent actions taken to reduce emissions from energy production, industry, and transportation, a new campaign substituting residential solid fuels with electricity or natural gas has been launched in Beijing, Tianjin, and 26 other municipalities in northern China, aiming at solving severe ambient air pollution in the region. Quantitative analysis shows that the campaign can accelerate residential energy transition significantly, and if the planned target can be achieved, more than 60% of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 42 publications
3
119
0
Order By: Relevance
“…The energy substitution was capable of generating large air pollution mitigation and human health benefits. 70 , 71 However, owing to the rush for quick results and inadequate planning and implementation, some areas in Hebei faced gas shortages, and basic winter heating supplies could not be guaranteed. 72 Policy makers will have to address the social and environmental justice issues of removing coal as an energy supply option among rural households.…”
Section: A Just Transition Away From Coalmentioning
confidence: 99%
“…The energy substitution was capable of generating large air pollution mitigation and human health benefits. 70 , 71 However, owing to the rush for quick results and inadequate planning and implementation, some areas in Hebei faced gas shortages, and basic winter heating supplies could not be guaranteed. 72 Policy makers will have to address the social and environmental justice issues of removing coal as an energy supply option among rural households.…”
Section: A Just Transition Away From Coalmentioning
confidence: 99%
“…Long-term exposure to the chemical components of PM 2.5 has not been well studied (Lepeule et al 2012), and we used the total PM 2.5 concentration to estimate premature deaths in the health impact function. The health impact model in our study has not considered indoor air pollution, which may underestimate health effects due to indoor coal combustion (Meng et al 2019). There is also less evidence for the relationship between O 3 and COPD.…”
Section: Caveatsmentioning
confidence: 88%
“…Moreover, big cities virtually eliminated use of coal (Guan et al, 2018;, while in rural areas use of coal even increased (Meng et al, 2019). For example, a national survey showed that China's rural residential coal consumption fractions for heating increased from 19.2% to 27.2% (Tao et al, 2018).…”
Section: Effects Of Spatial Disaggregation Methods On Spatial Distribmentioning
confidence: 99%